OLDER ADULTS' PARTICIPATION IN VALUED LEISURE ACTIVITIES BY CLUSTERS OF COMMON SYMPTOMS. (11th November 2018) - Liu, M; Perrin, N; Taylor, J; Okoye, S; Szanton, S
Abstract: Pain, insomnia, depression and anxiety are common in older adults and interfere with leisure activities. Few studies have examined interference with leisure activities based on associated symptoms. We conducted a cluster analysis to identify people with similar symptom clusters based on pain, insomnia, depression and anxiety in 7, 508 older adults using data from the National Health and Aging Trends Study. Chi-square tests were performed to describe 1) demographics and health-related factors; and 2) interference with valued leisure activities (visiting friends/family, attending religious services, participating in clubs/classes, and going out "for enjoyment") across clusters. We identified four clusters: 1-no symptoms (41%), 2-pain only (32%), 3-pain+moderate insomnia+mild depression+mild anxiety (17%), and 4-pain+moderate insomnia+severe depression+severe anxiety (10%). Compared to clusters 1 and 2, people experiencing clusters 3 and 4 tended to be older, Hispanic or non-Hispanic Black, female, have high school education or less, not live with a spouse, obese, and rate their health fair or poor. Older adults in this sample experienced interference with attending religious services (19%), participating in clubs/classes (11%), going out for enjoyment (9%) and visiting friends/family (8%). Interference with valued leisure activities differed across the clusters (all p<.001) with 6% – 17% of people in cluster 2 experiencing interference, 17 – 31% in cluster 3 and 26 – 48% in cluster 4. Insomnia and severity of depression and anxiety have a greater impact on valued leisure activities than pain only. Interventions targeting both number and severity of these symptoms may lead to increased participation in valued leisure activities.